Prison Religion: Exploring the Link Between Pre- and In-prison Experiences to Religious Activity - Said, Iman (Crime & delinquency, 2025)
Participation in prison-based religious programs has received a wealth of scholarly attention. Evidence shows that participation can provide critical coping mechanisms and access to a social support network. But despite a wealth of research, less work explores the pre-prison and in-prison attributes and experiences that may increase overall religious activity while in prison. We use data from the 2004 Survey of Inmates in State and Federal Correctional Facilities to explore the covariates of religious engagement, uncovering the critical role of adverse experiences including pre-prison physical abuse and in-prison depression. Our findings highlight the need to further explore the influence of extra religious attributes and contribute to scholarship on the role of faith based prison programing in the lives of incarcerated individuals.